Nutrient limitation as a strategy for increasing starch accumulation in microalgae - Dragone, Giuliano (2011)
Increasing microalgal starch content by nutrient limitation has been regarded as an affordable approach for the production of third generation bioethanol. This work evaluated starch accumulation in Chlorella vulgaris P12 under different initial concentrations of nitrogen (0–2.2 g urea L−1) and iron (0–0.08 g FeNa-EDTA L−1) sources, using a central composite design (CCD) for two factors. The obtained model: Starch content (%) = 8.220 − 16.133X1 + 13.850, relating starch accumulation in microalgae with the coded level for initial urea concentration in the growth medium (X1) presented a good concordance between the predicted and experimental values (R2 = 0.94). Since accumulation of starch occurred at nitrogen depletion conditions under which the cell growth was much slower than that observed during nitrogen supplemented cultivations, a two-stage cultivation process for high starch accumulation (>40%) and cell growth of C. vulgaris was proposed: a first cultivation stage using nitrogen- and iron-supplemented medium (initial urea and FeNa-EDTA concentrations of 1.1 and 0.08 g L−1, respectively), followed by a second cultivation stage in a nitrogen- and iron-free medium. The high starch content obtained suggests C. vulgaris P12 as a very promising feedstock for bioethanol production.